Educação, subjetivação e singularidade em Max Stirner - Figueiroa, Jonas Nogueira (Universidade Federal de São Carlos, 2013)
This study aims to problematize, based on a bibliographic study of the German philosopher Max Stirner, the modern paradigm on education, more precisely on the practical of subjectification that compose this paradigm and the possibilities of singularity, as a resistance method to this process. For this purpose, the current study aim to revisit the debate conducted by the author in his book The Ego and his Own, in which the modern subjectivity is presented as a result of a process that started in the antique times and the rise of christianity, pointing to the appearance of a specific type of rationality and morality, constitutive parts of that subjectivity. Moreover, the discussion turns to the characteristics that education acquires in Liberalism, pointing to a better understanding of the liberal education as a process constructing subjectivities, in which the modern rationality and morality occupy a central role to internalize and naturalize domination and governance used nowadays. Finally, we discuss the possibilities presented by the author to construct other relationships socially and pedagogically, besides the ones of subordination that define education in current times.
Keywords: Educação - filosofia; Stirner, Max, 1806-1856; Subjetivação; Singularidades; Anarquismo; Education; Subjectivity; Singularity; Anarchism; CIENCIAS HUMANAS::EDUCACAO